2021
DOI: 10.1001/jamanetworkopen.2021.31674
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Discrepancies Between Pulse Oximetry and Arterial Oxygen Saturation Measurements by Race and Ethnicity and Association With Organ Dysfunction and Mortality

Abstract: IMPORTANCE Discrepancies in oxygen saturation measured by pulse oximetry (SpO 2 ), when compared with arterial oxygen saturation (SaO 2 ) measured by arterial blood gas (ABG), may differentially affect patients according to race and ethnicity. However, the association of these disparities with health outcomes is unknown. OBJECTIVETo examine racial and ethnic discrepancies between SaO 2 and SpO 2 measures and their associations with clinical outcomes. DESIGN, SETTING, AND PARTICIPANTS This multicenter, retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
160
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(171 citation statements)
references
References 26 publications
8
160
3
Order By: Relevance
“… 20 However, the need for training ANNs to the full range of Fitzpatrick skin types I to VI is also indicated by recent observations in pulse oximetry, where darker skin results in a small but larger number of undetected hypoxemia events. 37 Furthermore, all measurements were performed on the volar forearm during occlusion provocations. Our results suggest that a training data set of 19 subjects is enough for training an algorithm that can estimate in low-pigmented forearm skin.…”
Section: Discussionmentioning
confidence: 99%
“… 20 However, the need for training ANNs to the full range of Fitzpatrick skin types I to VI is also indicated by recent observations in pulse oximetry, where darker skin results in a small but larger number of undetected hypoxemia events. 37 Furthermore, all measurements were performed on the volar forearm during occlusion provocations. Our results suggest that a training data set of 19 subjects is enough for training an algorithm that can estimate in low-pigmented forearm skin.…”
Section: Discussionmentioning
confidence: 99%
“…Underestimated SpO 2 readings also have the potential to be harmful, resulting in unnecessary treatment with oxygen (and the risk of hyperoxaemia) and wider impacts such as delayed hospital discharge. Two recent diagnostic studies provide evidence on clinical implications resulting from the bias in pulse oximetry for blood oxygen saturation levels[7,69]. In these studies people described as Black had a higher risk of ‘ occult hypoxemia that was not detected by pulse oximetry ’ compared with those described as White.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, seven studies considering the impact of skin pigmentation and eight studies considering ethnicity compared SpO 2 -SaO 2 bias data between different subgroups and presented only tests of significance results, rather than SpO 2 and SaO 2 data per se at each subgroup level. Also, at least two studies used diagnostic accuracy design that only presented proportions of participants with specific ranges of SpO 2 in relation to specific SaO 2 values, again rather than SpO 2 and SaO 2 data per se [7,69]. We contacted authors of these studies to request relevant data and received data for two studies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is potential for underlying issues regarding the accuracy of medical equipment across different populations. For example, it was shown that pulse oximeters were inaccurate for certain races, which came to light during the COVID crisis, resulting in hidden hypoxemia among patients of colour [18]. This was further investigated, and studies showed that oxygen saturation levels had greater variability in patients who identified as African American, followed by Hispanic, Asian, and lastly, Caucasian patients.…”
Section: Discussionmentioning
confidence: 99%